The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1938640019828069
|View full text |Cite
|
Sign up to set email alerts
|

Does Patient-Specific Instrumentation Have a Higher Rate of Early Osteolysis Than Standard Referencing Techniques in Total Ankle Arthroplasty? A Radiographic Analysis

Abstract: Introduction: Patient-specific instrumentation (PSI) has been developed for total ankle arthroplasty (TAA), with proven benefits. One concern regarding PSI is the need for more soft tissue dissection in order to accurately position the PSI guides, which has the theoretical disadvantage of increased osteolysis. The purpose of our study is to compare the incidence and magnitude of osteolysis for the INFINITY Total Ankle System between PSI and standard referencing (SR) techniques. Methods: Sixty-seven patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…This is of concern because it may carry the risk of impaired bony ingrowth of the implants. Escudero et al found a slightly higher, though not significant, risk of osteolysis in the PSI group compared with SR. 10 This agrees with our findings, wherein a trend for a higher risk for radiolucent lines was observed in the PSI group (2 vs 1 case in the SR group). However, the numbers in the current study are too low to conclude whether the increased intraoperative damage to the periarticular bone affects the incorporation of the implants in TAA, and more research is needed before a conclusion can be drawn.…”
Section: Discussionsupporting
confidence: 93%
“…This is of concern because it may carry the risk of impaired bony ingrowth of the implants. Escudero et al found a slightly higher, though not significant, risk of osteolysis in the PSI group compared with SR. 10 This agrees with our findings, wherein a trend for a higher risk for radiolucent lines was observed in the PSI group (2 vs 1 case in the SR group). However, the numbers in the current study are too low to conclude whether the increased intraoperative damage to the periarticular bone affects the incorporation of the implants in TAA, and more research is needed before a conclusion can be drawn.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike this present study, high rates of tibial component osteolysis have been reported in several studies ranging from 31% to 41%. 7,20…”
Section: Discussionmentioning
confidence: 99%
“…All 14 were examined for inclusion and exclusion, which resulted in 6 total published studies with clinical outcomes (Figure 1). 11,[14][15][16][17][18] All were retrospective. Four were level IV and 2 were level III studies.…”
Section: Resultsmentioning
confidence: 99%